2020
DOI: 10.3390/su12052064
|View full text |Cite
|
Sign up to set email alerts
|

Digital Platform/Mobile App to Boost Cycling for the Promotion of Sustainable Mobility in Mid-Sized Starter Cycling Cities

Abstract: According to the United Nations, cities will represent two-thirds of the world's population in 2050, which presents some challenges, especially to the transportation sector. To improve the population's quality of life and the sustainability of cities, mobility must be sustainable, and cycling will play an important role in achieving this. Literature shows that we can promote cycling with better infrastructures, through multimodality, and through behavioral changes. Promoting the use of bicycles through behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
0
9
1
2
Order By: Relevance
“…In relation to the BSS, it can be concluded that the benefits of the system to improve the conditions of bicycle use can be defined through a vast set of indicators, such as the number, distance, coverage area of the BSS stations and/or E-BSS, integration with other modes of transport, and the type and quantity of digital solutions associated with the service, among others [6,18,20,83].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the BSS, it can be concluded that the benefits of the system to improve the conditions of bicycle use can be defined through a vast set of indicators, such as the number, distance, coverage area of the BSS stations and/or E-BSS, integration with other modes of transport, and the type and quantity of digital solutions associated with the service, among others [6,18,20,83].…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive strategy to promote cycling in cities consists of developing policies, plans, and measures related to infrastructure, behavior, and the integration with other modes of transport, e.g., multimodality [6]. This work focused in cycle infrastructure dimension, considering the existing supply and types of cycling facilities, as well as the inherent level of perception of the quality, suitability, and the degree of importance of various characteristics of the cycling environment.…”
Section: Introductionmentioning
confidence: 99%
“…The pedestrian zones have been created since 1995 with the pedestrianization of the main streets of the city center, including the area of the Republic square and Souto street [80], and nowadays it counts more than 20,000 m 2 of area exclusively for pedestrian use [81]. The local government has been also assuming the need for better bicycle mobility infrastructure to achieve the sustainable mobility goals from the National Strategy for Active Mobility, which culminated in the creation of 22 km of cycling routes along with parking facilities to promote multimodality [82].…”
Section: Background Informationmentioning
confidence: 99%
“…Tailored messages and recommendations transformed the way mobility approaches environmental stewardship. Meireles and Riberiro's study showed that more than 60% of nonregular cyclists at the regional level considered smartphone apps to lead more people to use bicycles [164]. Cycling mobile apps should prioritize route calculation and location-based services associated with the built environment, according to the questionnaire.…”
Section: Mobile Technology In Transport Behaviormentioning
confidence: 99%